Fabrication of chitosan and polyvinyl alcohol blend membrane with different concentrations PEG 400 as additive - Winetta Arianty, Ariffin (2008)
In this research, Chitosan and Polyvinyl alcohol (PVA) blend membrane is made by adding additive which is polyethylene glycol or known as PEG and PEG concentration used in this research was PEG 400. The objective of this research is to study the performance and morphology of Chitosan and PVA blend with PEG 400 as additive using SEM, AFM, pure water permeation (PWP) and solute separation permeability. The membrane was prepared using dope solution method by blending Chitosan, PVA and PEG 400 together. Two difference concentration of PEG 400 which is 4 wt% and 6 wt% are use. Casting method take part after the blending process was finished. After the membrane is dried, it would be easy for the membrane to be peeled off. The membrane was characterized and distinguished by its performance in term of its pure water permeation (PWP) and solute separation and by its morphology using SEM and AFM. From the results, the pure water permeation rate of the membrane is higher by using high concentration of PEG 400 because of the increasing of the hydrophilicity of the membrane but decreasing its selectivity in solute separation. The morphology of the membrane at its cross-section can be seen using scanning electron microscopy (SEM). Characterization of membrane base on its surface section is done using atomic force microscopy (AFM).